Enantioselective Synthesis of cis‐2, 6‐Disubstituted‐4‐methylene Tetrahydropyrans via Chromium Catalysis†. Issue 12 (14th October 2020) - Bai, Jing; Chen, Bin; Zhang, Guozhu
Summary of main observation and conclusion: Enantioenriched 2, 6‐disubstituted 4‐methylene tetrahydropyrans have been obtained via a two‐step sequence consisting of a highly enantioselective chromium‐catalyzed carbonyl 2‐(trimethylsilyl methyl)allylation and Prins cyclization. Commercially available (2‐(chloromethyl)allyl)trimethylsilane serves as the bifunctional linchpin to combine two aldehydes to assemble the 2, 6‐disubstituted pyrans. A variety of functional groups are compatible under the mild reaction conditions. The synthetic utility of this methodology was demonstrated by the asymmetric synthesis of 16 examples of homoallylic alcohol and 8 examples of 2, 6‐disubstituted 4‐methylene tetrahydropyrans, including an advanced intermediate which could be transformed to natural product centrolobine via a known procedure. Abstract : Enantioenriched 2, 6‐disubstituted 4‐methylene tetrahydropyrans have been obtained via a two‐ step sequence consisting of a highly enantioselective chromium‐catalyzed carbonyl 2‐(trimethylsilyl methyl)allylation and Prins cyclization. Commercially available (2‐(chloromethyl)allyl)trimethylsilane serves as the bifunctional linchpin to combine two aldehydes to assemble the 2, 6‐disubstituted pyrans.